EFFECTIVENESS OF POSTPARTUM EXERCISES ON REDUCING INTERRECTI DISTANCE: A QUASI EXPERIMENTAL STUDY AMONG POSTPARTUM MOTHERS - Salma Nabilah Fauziyyah; Faizah Betty Rahayuningsih (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2025)
Diastasis rectus abdominis (DRA) is a common postpartum condition characterized by a widening of the inter-recti distance (IRD), which may lead to postural changes, lower back pain, and decreased quality of life. Postpartum exercise is a nonpharmacological intervention designed to strengthen abdominal muscles, improve core stability, and support the reduction of IRD. This study aims to analyze the effectiveness of postpartum exercises in reducing inter-recti distance and improving abdominal muscle recovery among postpartum women. A quasi-experimental pretestposttest control group design was conducted involving 90 postpartum women who met the inclusion and exclusion criteria. Participants were assigned to treatment and control groups, with the intervention group receiving validated postpartum exercise videos performed routinely for six weeks. IRD was measured using a standardized palpation technique with proven validity and reliability. Additional instruments included observation sheets, muscle strength assessments, pain scales, and a postpartum quality-of-life questionnaire using the MPQOL-I (Maternal Postpartum Quality of Life Instrument). Data were analyzed using paired t-tests and independent t-tests with statistical significance set at p < 0.05. A significant reduction in IRD was observed in the treatment group compared with the control group (p = 0.001). The treatment group demonstrated greater improvement in abdominal muscle approximation, indicating a positive effect of postpartum exercises on abdominal wall recovery. Postpartum exercise is effective in reducing inter-recti distance and promoting abdominal muscle recovery in postpartum women. It is recommended as a simple, safe, and evidence-based intervention for postpartum care.